Determining the Health State Utility Value of Urinary Tract Infection in Women. Issue 2 (March 2019) - Kalyanaraman, Rajeshwari; Demtchouk, Veronica; Iyer, Vidya; Patterson, Danielle
Abstract : Objectives: Health state utility values are a unique representation of an individual's valuation for being in a particular health state. Depending on the method of evaluation, group of patients, and setting, these values vary significantly. To date, majority of the available estimates for the health-related state utility values for urinary tract infection (UTI) has been in men with comorbid conditions such as benign prostatic hyperplasia and bladder cancer or with spinal cord abnormalities. The utility values in these studies ranged between 0.3 and 0.9. The purpose of this study was to determine and compare the health state utility value for UTI in women derived from EuroQol 5 dimensions (EQ-5D) questionnaire and visual analog scale (VAS) with the Standard Gamble (SG) interview in a tertiary medical center. Methods: Healthy volunteers at least 18 years of age with no history of UTI were approached for study participation. Twenty-five subjects were given a standard sheet describing UTI and its symptoms and were asked to complete the EQ-5D and VAS followed by SG conversation. Results: The median utility (interquartile range) for UTI varied based on the methods: EQ-5D, 1.00 (0.124); VAS, 0.98 (0.10); and SG, 0.90 (0.15). Spearman correlation showed that these values were weakly correlated. Conclusions: Our data suggest a value of 0.90 to represent the health state utility value of UTI in women older than 18 years. The EQ-5D is not sensitive to impact of UTI in women, and we would not recommend using it for that purpose based on our findings.